10 Years of Frontiers in materials: interface engineering for aqueous zinc-ion batteries - Yang, Jia-Ning; Tian, Han; Wang, Kai-Xue; Chen, Jie-Sheng (Frontiers in Materials, 2024)
Aqueous Zinc Ion Batteries (ZIBs), characterized by their high theoretical capacity, cost-effectiveness, and robust safety profile, stand out as one of the most promising contenders for the next generation of electrochemical energy storage applications. Nevertheless, the commercialization of ZIBs encounters obstacles of unsatisfactory energy density and suboptimal cycling stability, which are related to the unstable interfaces of Zn anodes and cathodes. Herein, the research advances in Zn anodes and cathode materials and corresponding interface engineering in recent years are systematically reviewed. The rationalization of these research can guide further investigations in the design of cathode/anode materials in ZIBs.